Measuring financial stress index for Turkey - Koyunlu, Ayşegül (İstanbul Bilgi Üniversitesi, 2019)
The aim of this study is to construct a financial stress index for Turkey by using different methods to evaluate whether the financial stress index that is constructed is successful in terms of predicting stressful time periods properly for the period between 2003-2018. In the literature, the measurement of the Financial Stress Index is commonly based on the banking sector, the foreign exchange market, the stock market, the bond market, and the public sector. Likewise, these indicators are used in this study, and also housing market indicator is added because deterioration in the housing market can have a systemic impact on the economy due to its relationship with the other markets. In this way, this study will contribute to the literature in terms of adding a relatively new variable in the measurement of financial stress. The 3-month TRLIBOR, foreign exchange market pressure index, the return of the Borsa Istanbul stock price index, 2-year government bond yields, Credit Default Swaps, and residential sales prices are the sub-components of the measurement of the financial stress in Turkey. The weighting scheme of those variables is based on three different methods. The equal-variance method is the most commonly used one which assumes every single market component has equal importance for all the financial system and also each component acts independently from each other. However, the principal component analysis takes into account the co-movement of the sub-market indicators in calculating financial stress. The standard portfolio theory considers the time-varying cross-correlations among the different stress indices. Furthermore, to measure volatilities for the banking sector equity index, currency, and the stock market, generalized autoregressive conditional heteroskedasticity models are used.

Bu çalışmanın amacı farklı metodlar kullanarak Türkiye için bir finansal stres endeski oluşturmak ve 2003-2018 dönemi için oluşturulan bu stres endeksinin ilgili zaman aralığında stres dönemlerini doğru tahmin edip etmediğini araştırmaktır. Literatürde finansal stresin ölçümünde genel olarak bankacılık sektörü, döviz piyasası, hisse senedi piyasası, bono piyasası ve kamu sektörü kullanılmaktadır. Benzer şekilde bu çalışmada da bu piyasalar kullanılmış olup, ayrıca diğer piyasalarla etkileşimden dolayı sistemik etkiye sahip olduğu düşünülen konut fiyat endeksi çalışmaya dahil edilmiştir. Böylelikle finansal stresin ölçümünde görece yeni bir değişken eklenerek literature katkı sağlayacağı düşünülmüştür. 3-aylık TRLIBOR, döviz piyasası baskı endeksi, 2-yıllık devlet tahvili getirileri, Kredi Temerrüt Takası ve konut satış fiyatları Türkiye için finansal stresin ölçümünde kullanılan alt bileşenlerdir. Değişkenlerin ağırlıklandırılması üç farklı metoda dayanmaktadır. Her bir alt bileşenin birbirinden bağımsız hareket ettiğini ve eşit öneme sahip olduğunu varsayan eşit-varyans ağırlıklandırma metodu en yaygın kullanılandır. Bununla birlikte temel bileşenler analizi, alt piyasa göstergelerinin birlikte hareketini göz önünde bulundurur. Standard portföy teorisi ise farklı stres bileşenleri arasındaki zamana göre değişen çapraz korelasyonları dikkate alır. BIST bankacılık sektörü, hisse senedi endeksi, döviz piyasası ve BIS100 hisse senedi getirilerine ait volatilitelerin hesaplanmasında GARCH modelleri kullanılmıştır